Food Processing: Advances in Thermal and Non-Thermal Technologies, Two Volume Set - Kshirod Kumar Dash; Sourav Chakraborty (CRC Press, 2021)
Advances in thermal and non-thermal food processing aims to discuss emerging trends based on the future scope and challenges and to explain uncertain challenges in food processing. In thermal processing different operations in food engineering namely advance drying methods, evaporation, extrusion cooking, different extraction techniques, crystallizations are covered in terms food engineering and process modeling aspect. For non-thermal processing, high pressure processing, ultrasound, ohmic heating, pulse electric field, pulse light technology, osmotic dehydration and so forth are discussed. Relevant mathematical modeling and numerical simulations has been included in every chapter. Features: Presents engineering focus on thermal and non-thermal food processing technologies. Discusses sub-classification for recent trends and relevant industry information/examples. Describes advances in drying, evaporation, blanching, crystallization and ohmic heating. Covers high-pressure processing, pulse electric field, pulse light technology, irradiation, and ultrasonic techniques. Includes mathematical modeling and numerical simulations. The book is aimed at graduate students, professionals in food engineering and food technology, biological systems engineering.